Challenges in Conducting Research in Pediatric Long-Term Care Facilities. (October 2014) - Larson, Elaine L.; Cohen, Bevin; Murray, Meghan; Saiman, Lisa
Background . Children residing in long-term care facilities (LTCFs) have complex medical problems and unique care needs, yet research in this setting is rare. As part of an intervention study to improve patient safety (Keep It Clean for Kids [KICK]), we describe the challenges encountered and recommend approaches to build a successful and sustained collaborative relationship between pediatric LTCFs and the research team. Methods . We implemented a program with 5 components: leadership commitment, active staff participation by the creation of KICK teams, workflow assessments, staff training in the World Health Organization's "5 Moments for Hand Hygiene, " and electronic monitoring and feedback to staff regarding hand hygiene practices. Results . Major challenges encountered were establishing trust, building research teams, enhancing staff participation, and engaging families and visitors. Approaches to deal with these challenges are discussed. Conclusions . Conducting research in pediatric LTCFs requires sustained commitment to dealing with challenges and establishing collaborative relationships with administrative and frontline staff.